The Great Power Competition Volume 3 Cyberspace: The Fifth Domain - Farhadi, Adib.; Sanders, Ronald P.; Masys, Anthony (Cham : Springer International Publishing : Imprint: Springer, 2022)
For millennia, humans waged war on land and sea. The 20th century opened the skies and the stars, introducing air and space as warfare domains. Now, the 21st century has revealed perhaps the most insidious domain of all: cyberspace, the fifth domain. A realm free of physical boundaries, cyberspace lies at the intersection of technology and psychology, where one cannot see one's enemy, and the most potent weapon is information. The third book in the Great Power Competition series, Cyberspace: The Fifth Domain, explores the emergence of cyberspace as a vector for espionage, sabotage, crime, and war. It examines how cyberspace rapidly evolved from a novelty to a weapon capable of influencing global economics and overthrowing regimes, wielded by nation-states and religious ideologies to stunning effect. Cyberspace: The Fifth Domain offers a candid look at the United States' role in cyberspace, offering realistic prescriptions for responding to international cyber threats on the tactical, strategic, and doctrinal levels, answering the questions of how can we respond to these threats versus how should we respond? What are the obstacles to and consequences of strategic and tactical response options? What technological solutions are on the horizon? Should the U.S. adopt a more multi-domain offensive posture that eschews the dominant "cyber vs. cyber" paradigm? To answer these questions, experts examine the technological threats to critical infrastructure; cyber operations strategy, tactics, and doctrine; information influence operations; the weaponization of social media; and much more.
1. How We Got Here: The Rise of Cyber Conflict from 1991 to 2021 -- 2. The Great Cyber Talent Competition -- 3. Alternate Reality: The Use of Disinformation to Normalize Extremism -- 4. The Future of Cyber-Enabled Influence Operations: Emergent Technologies, Misinformation, and the Destruction of Democracy -- 5. Cybersecurity and Strategic Deterrence -- 6. When the Levee Breaks: A Global Trend of Cyber-Physical and Cyber-Operational Attacks against Critical Infrastructure and Future Implications on the Great Power Competition -- 7. Cyber Threats to Critical Infrastructure -- 8. Are China and Russia on the Cyber Offensive in Latin American and the Caribbean? -- 9. Russian and Chinese Cyber Involvement with Latin America -- 10. Cyber Leadership and the Era of the Great Power Competition -- 11. Global Alliances & Partnerships in the Modern Great Power Competition -- 12. Pacific Partners: Security Cooperation in the Great Power Competition -- 13. Countering Violent Extremism in Cyber Space: A New Frontier for the Great Power Cooperation -- 14. Thinking Globally, Acting Locally - Why a Targeted Approach to Russia, China, and the Proxy Cyber War is a Global Solution -- 15. Leveraging Talent to Dominate in Cyber: An Army Perspective.
Keywords: Security, International; Security systems; Science-Social aspects; International relations; International Security Studies; Security Science and Technology; Science and Technology Studies; International Relations